Configural Processing of Biological Motion in Human Superior Temporal Sulcus - Thompson, James C; Clarke, Michele; Stewart, Tennille; Puce, Aina (The Journal of neuroscience, 2005)
Observers recognize subtle changes in the movements of others with relative ease. However, tracking a walking human is computationally difficult, because the degree of articulation is high and scene changes can temporarily occlude parts of the moving figure. Here, we used functional magnetic resonance imaging to test the hypothesis that the superior temporal sulcus (STS) uses form cues to aid biological movement tracking. The same 10 healthy subjects detected human gait changes in a walking mannequin in two experiments. In experiment 1, we tested the effects of configural change and occlusion. The walking mannequin was presented intact or with the limbs and torso apart in visual space and either unoccluded or occluded by a set of vertical white bars. In experiment 2, the effects of inversion and occlusion were investigated, using an intact walking mannequin. Subjects reliably detected gait changes under all stimulus conditions. The intact walker produced significantly greater activation in the STS, inferior temporal sulcus (ITS), and inferior parietal cortex relative to the apart walker, regardless of occlusion. Interestingly, STS and ITS activation to the upright versus inverted walker was not significantly different. In contrast, superior parietal lobule and parieto-occipital cortex showed greater activation to the apart relative to intact walker. In the absence of an intact body configuration, parietal cortex activity increased to the independent movements of the limbs and torso. Our data suggest that the STS may use a body configuration-based model to process biological movement, thus forming a representation that survives partial occlusion.